Structure of a normal seismogenic fault zone in carbonates: The Vado di Corno Fault, Campo Imperatore, Central Apennines (Italy). (September 2016) - Demurtas, Matteo; Fondriest, Michele; Balsamo, Fabrizio; Clemenzi, Luca; Storti, Fabrizio; Bistacchi, Andrea; Di Toro, Giulio
Abstract: The Vado di Corno Fault Zone (VCFZ) is an active extensional fault cutting through carbonates in the Italian Central Apennines. The fault zone was exhumed from ∼2 km depth and accommodated a normal throw of ∼2 km since Early-Pleistocene. In the studied area, the master fault of the VCFZ dips N210/54° and juxtaposes Quaternary colluvial deposits in the hangingwall with cataclastic dolostones in the footwall. Detailed mapping of the fault zone rocks within the ∼300 m thick footwall-block evidenced the presence of five main structural units (Low Strain Damage Zone, High Strain Damage Zone, Breccia Unit, Cataclastic Unit 1 and Cataclastic Unit 2). The Breccia Unit results from the Pleistocene extensional reactivation of a pre-existing Pliocene thrust. The Cataclastic Unit 1 forms a ∼40 m thick band lining the master fault and recording in-situ shattering due to the propagation of multiple seismic ruptures. Seismic faulting is suggested also by the occurrence of mirror-like slip surfaces, highly localized sheared calcite-bearing veins and fluidized cataclasites. The VCFZ architecture compares well with seismological studies of the L'Aquila 2009 seismic sequence (mainshock MW 6.1), which imaged the reactivation of shallow-seated low-angle normal faults (Breccia Unit) cut by major high-angle normal faults (Cataclastic Units). Highlights: Fault rock distribution of the VCFZ footwall-block was mapped in detail. Evidence of extensional reactivation of an older thrust zone was documented. Thick cataclastic bands are suggested to form by pulverization and cataclasis. Microstructural investigations testified the past seismicity of the VCFZ. Fault structure resembles the fault network activated by L'Aquila 2009 earthquake.